Auto-calibration method and performance analysis for noncircular sources based on instrumental sensors - Jie-xin YIN; Ying WU; Ding WANG (Tongxin xuebao)
An improved direction-finding algorithm for noncircular sources was proposed in the presence of angularly dependent gain and phase errors, which is called NC-ISM based on the fundamental principle of ISM (instrumental sen-sor method). Through the application of the extended data model of non-circular signals with maximum rate, the pro-posed algorithm enhances the information utilization leading to advancement of estimation accuracy and twice the num-ber of sources that can be distinguished. The performance study on NC-ISM proved the statistical consistency of the pa-rameter estimation, and a theoretical derivation for the closed-form expression of the mean square error (MSE) of NC-ISM estimation was presented under the influence of modeling errors of instrumental sensors by the first-order analysis. Therefore, the analysis can provide theoretical support for practical applications. The simulation results not only verify the effectiveness of theoretical derivation, but also illustrate that NC-ISM is more robust than ISM with respect to signal-to-noise ratio as well as modeling errors.